2018
DOI: 10.1007/s42417-018-0018-3
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Modelling and In Situ Modal Testing of an Offshore Wind Turbine

Abstract: Purpose Generating electricity from wind turbines is currently a viable option to meet the electric power requirements in many countries. The structure of offshore wind turbines is constantly subjected to external dynamic loads due to wind, waves and rotor loads due to the rotation of blades. The frequency content of these dynamic loads is in the range of natural frequencies of the wind turbine. Therefore, determining the in situ dynamic characteristics of a wind turbine is very beneficial, as it can lead to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Dynamic analyses were performed using implicit-explicit switching, with an initial implicit analysis to preload the structure, followed by dynamic excitation using the explicit solver, and finally followed by an implicit analysis to obtain the post-earthquake monotonic response. This numerical modelling scheme was chosen following work by Asnaashari et al 22 and Vieira et al 23 who demonstrated the effectiveness of 3D FE analysis to model grouted connections under static loads. Natural frequencies and modeshapes were determined using the Block Shift and Invert Lanczos method.…”
Section: Numerical Modellingmentioning
confidence: 99%
“…Dynamic analyses were performed using implicit-explicit switching, with an initial implicit analysis to preload the structure, followed by dynamic excitation using the explicit solver, and finally followed by an implicit analysis to obtain the post-earthquake monotonic response. This numerical modelling scheme was chosen following work by Asnaashari et al 22 and Vieira et al 23 who demonstrated the effectiveness of 3D FE analysis to model grouted connections under static loads. Natural frequencies and modeshapes were determined using the Block Shift and Invert Lanczos method.…”
Section: Numerical Modellingmentioning
confidence: 99%
“…It has been advocated that Rayleigh's energy method is a close approximation of the coupled FSI modelling, and thus, it can be used as a precursor to high-fidelity numerical modelling. Asnaashari et al [98] have numerically analyzed the frequency spectrum of an offshore wind turbine with a monopile foundation. Euler-Bernoulli beam element has been employed for carrying out FEA of the turbine tower and the transition piece.…”
Section: Wind Turbine Towermentioning
confidence: 99%